Spontaneous Tumor Lysis Syndrome in an Undifferentiated Uterine Sarcoma: A Case Report and Review of the Literature - Zahra Valizadeh; Parisa Farshchi (Clinical Case Reports)
ABSTRACT Tumor lysis syndrome (TLS), as an oncologic emergency, may rarely occur in patients with solid organ neoplasms and without previous cancer therapy. Physicians should be highly aware of the possibility of TLS, with special attention in patients having bulky tumors, irrespective of recent treatment with cytotoxic agents for its prompt prevention and treatment.